KONSEPSI HUMANISME PENDIDIKAN ISLAM DALAM KERANGKA TIPOLOGI MAZHAB FILSAFAT ISLAM - Adawiyah, Robiah; Nihayah, Rohatun (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
The dialectic of Islamic education philosophy, as viewed through the lenses of three main schools of thought - Peripatetic (mashsha'iya), Illuminationist (Isyraqiyah), and Sufi (Irfan) - revolves around the concept of theocentric humanism. This contrasts with the anthropocentric humanism prevalent in Western modern philosophy. In Western thought, humanism often emphasizes human-centered freedoms and rights. However, in Islamic philosophy, particularly within the framework of education, humanism takes on a theocentric dimension. This means that humanism is centered around and guided by the divine or the concept of God. The emphasis is not solely on human autonomy and freedom but also on aligning human actions and aspirations with divine guidance and purpose. In summary, the philosophy of Islamic education as articulated by scholars thought reflects a theocentric humanism that emphasizes the spiritual and intellectual dimensions of human existence, affirming that true education is ultimately about aligning oneself with the divine will and wisdom.